Long Non-coding RNA LINC-PINT Suppresses Cell Proliferation and Migration of Melanoma via Recruiting EZH2 - Xu, Yangfan; Wang, Huixue; Li, Fang; Heindl, Ludwig M.; He, Xiaoyu; Yu, Jie; Yang, Jie; Ge, Shengfang; Ruan, Jing; Jia, Renbing; Fan, Xianqun (Frontiers in Cell and Developmental Biology, 2019)
Long non-coding RNAs (lncRNAs) have been identified as crucial regulators in many human cancers. Many lncRNAs show aberrant expression in cancer, and some of them play critical roles in tumor proliferation, invasion, and metastasis. However, the regulatory functions of lncRNAs in melanoma progression remain to be elucidated. We utilized the Real-time PCR methodology to determine the expression of LINC-PINT in melanoma cell lines. To evaluate the effect of LINC-PINT on tumorigenesis of melanoma, we used Cell Counting Kit-8 (CCK8) and colony formation assay. Flow cytometry assay was used to detect the function of LINC-PINT on cell cycle status. PINT-interacting proteins were identified by chromatin isolation using RNA purification (ChIRP).Microarray assay and bioinformatics analysis were used to find the potential target genes of LINC-PINT and the status of LINC-PINT target gene candidate was verified using chromatin immunoprecipitation assay (ChIP). LINC-PINT plays a role in suppressing the tumorigenicity of melanoma, which was further determined by xenograft model assay.